The interaction between wheat and pea protein influences the final chemical and sensory characteristics of extruded high moisture meat analogs - Richter, Jana K. (2023)
Plant-based meat analog products, including those produced by extrusion processing, have become increasingly popular. Complete comprehension of the texturization mechanism and the formation of fibrousness would help improve existing products and extend the variety of plant sources used. Therefore, this study aimed to provide improved insight into the mechanism of texturization during the processing of high-moisture meat analog (HMMA) products. Blends with different wheat and pea protein ratios (100:0, 80:20, 60:40, 40:60, 20:80, and 0:100 wheat:pea) were extruded at a screw speed of 400 rpm, two different moisture contents (50% and 55%), and a feed rate of 90 g/min using a co-rotating twin-screw extruder. Extrudates were analyzed for their texture, free sulfhydryl groups, disulfide bonds, and solubility in different extractants relative to the raw ingredient blends. In addition, a sensory analysis was conducted using the rapid and cost-effective “rate-all-that-apply” (RATA) methodology. The interplay between the two protein types had synergistic effects on the system parameters torque, pressure, and specific mechanical energy, as well as on some textural and sensory parameters. Molecular analyses were not influenced by the interplay between wheat and pea protein as the molecular analyses followed linear trends with the pea inclusion level. Analysis of protein solubility suggests that the texturization mechanism differs slightly depending on the protein type. It is suggested that the texturization of wheat protein depends highly on disulfide bonds, whereas the texturization of pea protein relies on the combination of disulfide bonds and non-covalent interactions. Additionally, RATA was found to be a valuable tool for HMMA products.